Development And Characterization Of Biomass Steam Boiler For Externally Fired Micro Gas Turbine (EFMGT) System - Azman, Amirul Azim (Universiti Sains Malaysia, 2018)
Alternative fuels are a priority in energy research field, due to issues of fossil fuel depletion and environmental degradation. Biomass is an important renewable energy fuel source for thermal and power applications, especially in countries like Malaysia where abundant biomass waste available. As for electrical power generation, interest has recently increased in small scale distributed generation (DG) due to its advantages over centralized power generation. Internal combustion (IC) engines, externally fired micro gas turbines (EFMGT) and wind turbines are the main candidates for DG technology. Boiler fueled biomass for EFMGT have shown success for power generation. This research developed and characterized a biomass steam boiler for EFMGT system. The EFMGT unites two advantages. On the one hand, the utilisation of the waste heat from the turbine in a recuperative process and, on the other, the possibility to burn “dirty” fuel. In particular, the EFMGT opens a new option to utilise biomass for combined-heat-and-power and contributes to reduce greenhouse gas emissions. The boiler is a monotube with counter flow configuration. The chosen tube material is copper with diameter and length of 10 mm and 120 m respectively. The combustion chamber is built up of bricks and refractory cement. The dimensions are 0.57 m internal diameter and 0.2 m height. The auxiliary equipments involved are, pump, motor, and blower with inverter controller. The design of boiler is tested throughout the experiment. The main target is targetting the produced of 2 kg/min steam and fortunately it achieve higher than expected. This boiler can produced up to 2.8 kg/min with steady state of steam and minimum of 1 kg/min with steady state of steam. The efficiency range is 93% to 98% depends on the water flow rate or input power.